Evaluasi dan Rekomendasi Peningkatan User Interface dan User Experience pada Aplikasi Prime Video Mobile - Kurniawan, Muhammad Yoga; Dirgahayu, Teduh (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
During the pandemic, Indonesia experienced developments in internet use, one of which was in the world of entertainment. This increase rate reached 78.19%. The entertainment that Indonesian people like during the pandemic is watching films or TV series. One application that provides online film streaming services is Prime Video. Prime Video is a film or TV series streaming application developed by Amazon in 2006. Based on data on the Play Store for this application, the rating obtained is 3.5 out of 5. According to several reviews from users, users find it difficult to log in and complain about bad app UI. User Interface is the appearance of a product such as color, layout and writing which functions to connect the system with the user. User Experience is an experience or experience that arises from users who have used a product or application that has been developed. The aim of this research is to increase the usability value of the Prime Video application by carrying out evaluation and redesign. The method used in this research is the data collection method, this method requires researchers to collect data both from related theories and previous research, as well as data obtained from respondents. After conducting interviews, the results were obtained that this application still had several shortcomings in the user interface and user experience. After carrying out the SUS test on 5 respondents regarding the Prime Video application, this application received a score of 65.5 and received a Bad rating. After obtaining the required data, the next process is the redesign process, this process is carried out by considering previous problems. After carrying out all the tests, results can be obtained and it can be concluded that the data collection method can help researchers to carry out evaluations and provide recommendations for improvements for the application. This research also produces a design plan that can be used as a recommendation to increase the usability value of the application.